Myopenic obesity determined by visceral fat area strongly predicts long-term mortality in cirrhosis. Issue 4 (April 2021) - Feng, Hongjuan; Wang, Xiaoyu; Zhao, Tianming; Mao, Lihong; Hui, Yangyang; Fan, Xiaofei; Lin, Lin; Zhao, Wei; Jiang, Kui; Wang, Bangmao; Yu, Qingxiang; Zhang, Jie; et al.
Summary: Background: The impact of changes in body composition has proved to correlate with outcomes in cirrhosis, however, numerous issues remain elusive. The present study aimed to investigate the prognostic value of myopenic obesity (MO) on long-term mortality in cirrhosis. Methods: We retrospectively analyzed 200 patients with cirrhosis. Body composition parameters including skeletal muscle index (SMI) and visceral fat area (VFA) were estimated by computed tomography images at the third lumbar vertebra level. We defined MO as a low SMI (male: SMI < 46.96 cm 2 /m 2 and female: SMI < 32.46 cm 2 /m 2 ) with BMI ≥ 25 kg/m 2 or VFA ≥ 100 cm 2 according to our previous publication. Patients were categorized into one of four body composition groups in terms of the presence or absence of myopenia and obesity. Results: On the basis of VFA or BMI, the four group comparison demonstrated the prognosis was poor in MO, followed by myopenic/nonobesity (MN), nonmyopenic/obesity and nonmyopenic/nonobesity, in that order (log-rank test). Multivariate Cox analysis identified that MO (HR 2.498; 95% CI, 1.214–5.140; P = 0.013), MN (HR 2.763; 95% CI, 1.244–6.134; P = 0.013), age (HR 3.035; 95% CI, 1.904–4.839; P < 0.001), neutrophil-to-lymphocyte ratio (HR 1.142; 95% CI, 1.082–1.207; P < 0.001) and MELD (HR 1.140; 95% CI, 1.066–1.219; P = 0.001) were independently associated with 2-year mortality according to VFA classification. Conclusions: MO was an independent predictor of higher long-term mortality in cirrhosis. Prevention strategies by reducing visceral fat obesity rather than BMI should be the optimal target for MO management.